2009
DOI: 10.1007/s10681-009-9984-6
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic correlations, G × E interactions and broad sense heritability analysis of grain and flour quality characteristics in high latitude spring bread wheats from Kazakhstan and Siberia

Abstract: Grain and flour samples of 42 high latitude spring bread wheat genotypes from Kazakhstan and Siberia evaluated in a multi-location trial were analyzed for grain concentrations of protein, zinc (Zn) and iron (Fe), as well as flour quality characteristics. The genotypes showed high grain protein concentrations (14-19%), but low dough strength was a common feature for most of them. Significant positive correlations were found between grain protein and flour protein, gluten, gliadin, gli/glu ratio, Zn, and Fe cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…The results of the amino acid profile analyses indicated that 38% of the total CP was essential amino acid (EAAs) (threonine, cysteine, tyrosine, valine, Zn content of the outer layer, Zn penetrated to the inner layers of rice grain. [39] These findings are in accordance with the findings of Zhao and Selim [43], Cakmak et al [44], Gomez-Becerra et al [45] and Phattarakul et al [39], which reported that the distribution patterns of protein bodies in the different fractions of the grain, such as embryo, endosperm and bran were closely related to their n, Fe and Zn content. [46] amino acids accumulation in grain.…”
Section: Amino Acid Profilessupporting
confidence: 88%
See 1 more Smart Citation
“…The results of the amino acid profile analyses indicated that 38% of the total CP was essential amino acid (EAAs) (threonine, cysteine, tyrosine, valine, Zn content of the outer layer, Zn penetrated to the inner layers of rice grain. [39] These findings are in accordance with the findings of Zhao and Selim [43], Cakmak et al [44], Gomez-Becerra et al [45] and Phattarakul et al [39], which reported that the distribution patterns of protein bodies in the different fractions of the grain, such as embryo, endosperm and bran were closely related to their n, Fe and Zn content. [46] amino acids accumulation in grain.…”
Section: Amino Acid Profilessupporting
confidence: 88%
“…Many researchers were found out that the grain Zn concentration in cereal crops was significantly correlated with grain protein content. [43][44][45] The correlation analysis between Zn and crude protein content in different parts of the grain indicated that the grain Zn was positively and significantly correlated to bran Zn (0.93**) and white rice Zn (0.91**) (Table 11). Also, the grain Zn content was significantly correlated with the CP content of bran (0.42*) and white rice (0.514*) ( Table 11).…”
Section: Yield and Yield Componentsmentioning
confidence: 99%
“…They evaluate the most promising germplasm and verify that varieties proposed for test marketing and commercialization comply with consumer preferred end-use quality attributes and are widely adapted and stable across sites and generations. While variances are associated with environmental effects [10,82,83,84,85,86], several elite materials have been identified with high heritability for zinc and iron concentrations across environments [15,81]. Research efforts continue to identify quantitative trait loci (QTLs) associated with grain zinc content and examine how to increase zinc loading in the grain [80,87,88,89,90].…”
Section: Zinc Wheatmentioning
confidence: 99%
“…The variation of the quality indices when growing each individual variety under different environments is always helpful both for the distribution of the new varieties and for their improvement in breeding programs (Gomez-Becera et al, 2010). The data on the variation of winter wheat quality is contradictable with regard to the level of genotype effect (Gomez-Beccera et al, 2010;Williams et al, 2008). In breeding there is always the question whether the high quality of a given variety under favorable environments is a prerequisite for the realization of its high-quality potential under unfavorable environments, too, or is it and impediment for its stability (Hristov et al, 2010;Tsenov et al, 2004).…”
Section: Evaluation Of Genotype Environment and Their Interaction Fomentioning
confidence: 99%